2021
DOI: 10.1038/s41586-021-03550-y
|View full text |Cite
|
Sign up to set email alerts
|

Widespread deoxygenation of temperate lakes

Abstract: The concentration of dissolved oxygen in aquatic systems helps regulate biodiveristy 1, 2 , nutrient biogeochemistry 3 , greenhouse gas emissions 4 , and drinking water quality 5 . The long-term declines in dissolved oxygen concentrations in coastal and ocean waters have been linked to climate warming and human activity 6, 7 , but little is known about changes in dissolved oxygen concentrations in lakes. While dissolved oxygen solubility decreases with increasing water temperatures, long-term lake trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
257
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 386 publications
(259 citation statements)
references
References 42 publications
2
257
0
Order By: Relevance
“…Using a different approach [4,68,69] reported warming at similar rates using in situ LSWT data for European lakes and the Great Lakes of North America. A more recent study by Jane et al [9] achieved similar results, estimating rates of 0.036 • C/year using in situ data on surface temperatures of lakes worldwide.…”
Section: Seasonal Trend Analysis Of Modis Lswt Timeseriesmentioning
confidence: 60%
See 3 more Smart Citations
“…Using a different approach [4,68,69] reported warming at similar rates using in situ LSWT data for European lakes and the Great Lakes of North America. A more recent study by Jane et al [9] achieved similar results, estimating rates of 0.036 • C/year using in situ data on surface temperatures of lakes worldwide.…”
Section: Seasonal Trend Analysis Of Modis Lswt Timeseriesmentioning
confidence: 60%
“…Nevertheless, it is interesting that around that time, much attention was given to the lake due to an increased frequency of algal blooms [63,64], the main causes of which were attributed to anthropogenic factors that influenced the water quality of the lake, which resulted in Decree 19 (2013) to protect the environmental quality of the lakes waters [65]. Recent studies indicate that warming trends in lakes, due to global warming, result in increasing oxygen loss that lead to higher phosphorous release from sediments; increasing oxygen depletion in deeper zones of lakes with thermal stratification patters [9]. The same article reported that some lakes present rising oxygen concentration near the surface with increased temperatures, particularly in lakes that have undergone nutrient enrichment from agriculture and urbanization, resulting in algal growth.…”
Section: Monthly Trend Analysis Of Modis Lswt Time Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to boost phytoplankton blooms, heat waves have many adverse effects on lake ecosystem. First, enhanced stratification associated with climate warming and heat waves resulted in the deoxygenation of bottom waters and oxygen losses (Bartosiewicz et al 2019 ; Jane et al 2021 ; Zhang et al 2015 ). Thermal stratification affected the vertical distribution of dissolved oxygen and expanded the area of the hypoxic-anoxic zone.…”
Section: Discussionmentioning
confidence: 99%